Missing mass spectra in hadronic events from e+e- collisions at √s = 161–172 GeV and limits on invisible Higgs decays - Dova, María Teresa (1998)
Events characterised by large hadronic energy and transverse momentum are selected from the data collected by the L3 detector at LEP at centre-of-mass energies between 161 and 172 GeV, corresponding to an integrated luminosity of 21 pb−1. The visible mass and the missing mass distributions of the selected events are consistent with those expected from Standard Model processes. This result is combined with that from data taken at the Z resonance to set an upper limit on the production rate and decay into invisible final states of a non-minimal Higgs boson, as a function of the Higgs mass. Assuming the non-minimal Higgs production cross section to be the same as for the Standard Model Higgs boson and the decay branching fraction into invisible final states to be 100%, a Higgs mass lower limit of 69.6 GeV is derived at 95% confidence level.